TNF-α Increase in a Cohort of Depressive Patients. (15th March 2021) - Groh, Adrian; Jahn, Kirsten; Walter, Marc; Heck, Johannes; Lichtinghagen, Ralf; Janke, Eva; L, Schulze Westhoff M.; Deest, Maximillian; Frieling, Helge; Bleich, Stefan; Kahl, Kai G.; Heberlein, Annemarie
Abstract : Background . The model of neuroinflammation has been proposed as a possible explanation of depression. Investigations of serum levels of tumor necrosis factor- α (TNF- α ) in depressed patients have previously shown contradictory results of increased and decreased levels of TNF- α during the treatment of depression. Methods . We compared the serum levels of TNF- α in two cohorts of patients suffering from depression (ICD-10 criteria): one cohort from a psychotherapeutic unit (n = 18 ), where patients were treated with Cognitive Behavioral Analysis System of Psychotherapy (CBASP), and the other cohort from a psychiatric day care unit (n = 16 ). Both cohorts were investigated at the beginning and at the end of treatment. The intensity of depression was measured by means of the Beck Depression Inventory, 2 nd edition (BDI-II) at both time points. Results . We observed a statistically significant increase of TNF- α in the psychotherapeutic unit at time point 2 compared to time point 1 (T = − 14.71, p < 0.001 ), but not in the psychiatric day care unit. In both cohorts, BDI-II scores at time point 2 were significantly decreased compared to time point 1 (psychiatric day care unit: T = 3.32, p = 0.005 ; psychotherapeutic unit: T = 6.22, p < 0.001 ). There was a significant correlation in the psychotherapeutic unit at time point 2 (r = − 0.682, p = 0.02 ). Conclusion . As TNF- α was increased at time point 2 in the psychotherapeutic unit but not in patients of the psychiatric day care unit, we propose the different durations of pretreatments in both cohorts and the associated processes of neuroinflammation as a possible explanation for our results. The lack of information about the time course of TNF- α in depression could in general explain the huge variety of TNF- α levels in different cohorts of depressed patients reported in the literature.